1991
DOI: 10.1149/1.2085876
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wafer Cleaning and Oxide Etching Using Vapor‐Phase Hydrogen Fluoride

Abstract: The vapor-phase hydrogen fluoride etch of oxides and nitride of silicon have been studied. A new mode of oxide selectivity, not possible with aqueous HF-based processes, gives rise to novel processes with practical applications. The inherent cleanliness and the resulting four to five times improvement in the electrical stress endurance of thin oxides make the vapor-phase process a viable substitute for the traditional processes based on aqueous HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…A simple HF vapor etches SiO 2 . [15][16][17][18] Etching here is characterized by a different oxide with a different ER, 19) alcohol hydrating the SiO 2 surface, and enhanced SiO 2 etching. 20) The etch rate is moderate, 10 to 500 nm min −1 , and we find a reactionlimiting space with high selectivity to nitride.…”
Section: Ale For Isotropic Etchingmentioning
confidence: 99%
“…A simple HF vapor etches SiO 2 . [15][16][17][18] Etching here is characterized by a different oxide with a different ER, 19) alcohol hydrating the SiO 2 surface, and enhanced SiO 2 etching. 20) The etch rate is moderate, 10 to 500 nm min −1 , and we find a reactionlimiting space with high selectivity to nitride.…”
Section: Ale For Isotropic Etchingmentioning
confidence: 99%
“…14) As a result, the etching does not exhibit good top-to-bottom uniformity. The third candidate is gas-phase etching, which utilizes anhydrous HF gas [15][16][17][18][19][20][21][22][23][24][25] and ClF 3 gas. [26][27][28] Although the reactivity of these gases is lower than that of fluorine radicals, enough etchant can be supplied diffusively in high aspect patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding gas-phase etching for SiO 2 , HF vapor etching has been investigated for microelectromechanical systems (MEMS) devices in the context of sacrificial oxide removal. [21][22][23] It was reported that the etching rate depends on the type of SiO 2 film 16) and that it can be enhanced by adding alcohol. 17,18) The etching mechanism of gas etching by HF has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been investigated for in situ cleaning prior to silicon epitaxial growth. These cleaning methods include thermally assisted cleaning [1], photo assisted cleaning [2][3][4][5][6][7], plasma assisted cleaning [8][9][10][11][12] and HF vapor cleaning [13]. Problems with conventional thermal process executed by using H 2 gas at a high substrate temperature of more than 800℃ for removal of native oxide and organic contaminants are that it cannot desorb the residual carbon contaminant and SiC precipitates are formed which are the origin of strain in the epitaxial film.…”
Section: Introductionmentioning
confidence: 99%